Online Learning to Rank: Absolute vs. Relative - Chen, Yiwei; Hofmann, Katja (Proceedings of the 24th international conference on World Wide Web (WWW), 2015)
Online learning to rank holds great promise for learning personalized search result rankings. First algorithms have been proposed, namely absolute feedback approaches, based on contextual bandits learning; and relative feedback approaches, based on gradient methods and inferred preferences between complete result rankings. Both types of approaches have shown promise, but they have not previously been compared to each other. It is therefore unclear which type of approach is the most suitable for which online learning to rank problems. In this work we present the first empirical comparison of absolute and relative online learning to rank approaches.